2020
DOI: 10.1007/s00784-020-03584-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laser monotherapy or non-surgical mechanical instrumentation in the management of untreated periodontitis patients. A systematic review and meta-analysis

Abstract: Objective To evaluate and compare the effects of laser monotherapy with non-surgical mechanical instrumentation alone in untreated periodontitis patients. Materials and methods A focused question was formulated based on the Population, Intervention, Comparison, Outcome, and Study design criteria (PICOS): in patients with untreated periodontitis, does laser mono-therapy provide adjunctive effects on pocket probing depth (PPD) changes compared with non-surgical instrumentation alone? Both randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…In terms of non-surgical periodontal treatment, laser use aims mainly in root surface detoxification. A recent systematic review and meta-analysis showed that in untreated periodontitis patients, laser monotherapy leads to similar clinical improvement to conventional non-surgical periodontal treatment alone [ 29 ], which is in agreement with earlier reviews [ 27 , 34 ]. Systematic reviews on untreated periodontitis failed to show further clinical benefits with the addition of laser treatment to conventional non-surgical periodontal treatment [ 27 , 28 , 30 ].…”
Section: The Use Of Lasers In Clinical Dentistrysupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of non-surgical periodontal treatment, laser use aims mainly in root surface detoxification. A recent systematic review and meta-analysis showed that in untreated periodontitis patients, laser monotherapy leads to similar clinical improvement to conventional non-surgical periodontal treatment alone [ 29 ], which is in agreement with earlier reviews [ 27 , 34 ]. Systematic reviews on untreated periodontitis failed to show further clinical benefits with the addition of laser treatment to conventional non-surgical periodontal treatment [ 27 , 28 , 30 ].…”
Section: The Use Of Lasers In Clinical Dentistrysupporting
confidence: 87%
“…Lasers are used in most areas of clinical dentistry and their use is steadily increasing. Their application includes caries detection, caries removal, dental cavity preparation, dentine hypersensitivity management, tooth bleaching, photodynamic therapy, excisional biopsy, aphthous ulcers management, frenectomy, vestibuloplasty, removal of irritation fibroma, removal of hyperplastic tissues, haemangioma, exposure of impacted teeth, gingivectomy and gingivoplasty, apicoectomy, an adjunct to endodontic treatment [ 19 ], gingival melanin hyperpigmentation removal [ 20 , 21 , 22 ], non-surgical periodontal treatment of untreated periodontitis [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and treatment of peri-implant diseases [ 31 , 32 , 33 ]. In terms of endodontic treatment, lasers are used for post-chemomechanical preparation to reduce the remaining bacterial load either by direct irradiation of the canal walls or by laser assisted irrigation via erbium laser group.…”
Section: The Use Of Lasers In Clinical Dentistrymentioning
confidence: 99%
“…If it is decided to treat MRONJ conservatively, the dental hygienist (on the advice of the dentist) could play a central role in all bio-stimulation procedures. These may be performed using ozone-generating instruments or laser therapy [2,[65][66][67][68][69][70][71][72]. The application of ozone therapy deploys various aids and methods (e.g.…”
Section: Stepmentioning
confidence: 99%
“…low level laser therapy, LLLT) would seem to be effective in increasing the organic bone matrix in the proximity of the lesion, in stimulating the growth of blood and lymph vessels inside and outside the gum line and in reducing pain and possibly also the size of adjacent bone exposure. And this is in addition to its characteristics of being a safe, minimally invasive and well-tolerated technique [68][69][70][71][72]. Many authors have reported clinical success in the treatment of MRONJ with LLLT, deploying different wavelengths and different parameters [73,74].…”
Section: Stepmentioning
confidence: 99%
“…Erbium-doped yttrium–aluminum–garnet (Er:YAG) laser irradiation has been suggested to be a better treatment option for implant surface decontamination to control peri-implantitis because of its numerous advantages, including dental calculus removal, high bactericidal activity, excellent tissue ablation, and promoting of new bone formation [ 6 ]. Er:YAG laser has been extensively investigated for applications in clinical treatment of peri-implantitis either independently or in combination with other techniques, showing favorable outcomes [ 7 ]. However, there is no consensus on the optimal Er:YAG laser irradiation parameters for debridement of microstructured surfaces of titanium implants, particularly at a high pulse repetition rate [ 8 ].…”
Section: Introductionmentioning
confidence: 99%